Independent Chraracter of 5-6 Years Old Children in Learning Activities at School and Activities at Home - Sartika Kale; Minjte Ratoe Oedjoe; Harlenci Y. Metha (Universitas Nusa Cendana, 2022)
Not all children are able to show optimal independence character at TK Beringin Jaya Maf. For this reason, this study aims to find out more about the forms of independence character from children in TK Beringin Jaya Maf which is considered not optimal character of independence, so that it can be analyzed the extent of the child's level of independence, as well as factors that affect the development of the child's own independence character. The participants in the study were four children aged 5-6 years, four parents of students, and one Group B teacher. Data is taken using observation and interview techniques. The results found are forms of character independence of children aged 5-6 years at TK Beringin Jaya Maf shown with children able to wash their hands, wear their own shoes and clean toys at school. At home, children are able to show independent character when eating, drinking, wearing clothes, bathing and brushing their teeth. Factors that affect the form of the child's independence character are habituation factors, parental busyness and other adult actions around the child. Although the independence that children show is not optimal and consistent, but children have taken the initiative to start completing simple tasks both at home and at school.